Effect of Mn2+ substitution into the hst lattice of ZnO via sol-gel route for boosting the dye-sensitized solar cells performance - Kumbhar, Deepak; Delekar, Sagar; Kumbhar, Sarita; Dhodamani, Ananta; Harale, Namdev; Nalawade, Rekha; Nalawade, Avinash (Chemical Papers, 2021)
In this study, Mn2+ ion is doped in ZnO lattice framework at 1, 3 and 5 wt % by a simple and low-cost sol-gel route to attain improved optoelectronic response. The structural investigation by XRD and Raman analysis explores the formation of hexagonal wurtzite framework with variations in lattice parameters comprising peak intensities favors the Mn doping. The extent of doping was supported by EDS analysis, while XPS confirms doping in + 2 chemical state. The optical investigation by UV-visible and PL provides prominent peaks that also specify peak shifting in order of doping level, while the significant hexagon-shaped nanoparticle (NP) formation was deduced in SEM and TEM micrographs. These proficient ZnO NPs have been deposited on fluorine-doped tin oxide (FTO) conducting glass plate by doctor-blade technique to get photoanodes. The electrical performance of these photoanodes especially photocurrent generation was investigated under standard AM 1.5 one sun illuminations. The highest photoconversion efficiency was attained for 3% Mn-doped ZnO photoanode after xanthene-based organic dye sensitization with output efficiency (eta%) of 0.25% higher than 0.03% of bare ZnO. The comparable ionic radii with exactly half-filled 3d orbital simply overlap with the ZnO valence bond responsible for enhanced overall structural and optical properties that beneficial for DSSCs performance.
Keywords: gel; Mixed dye; Mn-doped ZnO; Photoelectrochemical cell; Sol&#8211

Effect of Mn2+ substitution into the hst lattice of ZnO via sol-gel route for boosting the dye-sensitized solar cells performance (Apr, 10.1007/s11696-021-01615-w, 2021) - Kumbhar, Deepak; Delekar, Sagar; Kumbhar, Sarita; Dhodamani, Ananta; Harale, Namdev; Nalawade, Rekha; Nalawade, Avinash (Chemical Papers, 2021)

Enhanced photoelectrochemical cell performance of Co doped ZnO nanoparticles sensitized by affordable mixed dyes as sensitizer - Kumbhar, Deepak; Kumbhar, Sarita; Dhodamani, Anant; Delekar, Sagar; Harale, Namdev; Nalawade, Rekha; Nalawade, Avinash (Inorganic and Nano-Metal Chemistry, 2021)
In the present investigation, a simple sol-gel approach has been employed for the synthesis of hexagonal wurtzite ZnO nanoparticles (NPs). X-ray diffraction (XRD) rietveld study and Raman analysis reveal the mislaid of the mixed phases of ZnO NPs after doping. The scanning electron micrographs and transmission electron microscopy confirm the formation of hexagonal disk-shaped NPs. FTIR, PL, EDX, XPS validate optical and stoichiometric concentration of Co in ZnO lattice. UV-visible DRS study shows absorption edge with humps to the red region of the spectrum with increasing the absorption strength and shortening of band gap as the content of Co (II) increases. Finally, the prepared samples were coated on the surface of cleaned FTO substrate through a simple doctor blade technique and sensitized with prepared dye. The ZnO photoanode shows 0.036% of efficiency (eta%) while the photoanodes of Co doped samples expose the enhanced efficiencies of 0.29%, 0.389%, 0.089%.
Keywords: Co doped ZnO; mixed dyes as sensitizer; Photoelectrochemical cell; sol-gel